Comments on "preparation and transport properties of novel lithium ionic liquids [electrochim. Acta 50 (2004) 1–5]" and "ion transport properties of lithium ionic liquids and their ion gels. [Electrochim. acta 50 (2005) 3872–3877]". (20th March 2020) - Harris, Kenneth R.
Abstract: Some years ago, Shobukawa et al. published transport data for a number of lithium salts with complex borate anions having oligoether groups substituted on the central boron atom. It is the purpose of this Comment to show that the data are consistent with cation-anion association as deduced from the Laity resistance coefficients of non-equilibrium thermodynamics. This is most likely due to strong lithium interactions with the oxygen atoms of the ether linkages which has also been postulated in studies of lithium salt-phosphonium ionic liquid mixtures where the cations have similar ether linkages.